Exploring Innovation Capability to Enhance Marketing Performance of Culinary MSMEs in Pekanbaru City - rosmita; Ujang Paman Ismail; Annisa Mardatillah (Jurnal Bisnis dan Manajemen, 2025)
This study aims to explore innovation capability in enhancing the marketing performance of culinary Micro, Small, and Medium Enterprises (MSMEs) in Pekanbaru City. Shifts in consumer behavior and increasing competition require MSMEs to develop innovative capabilities in order to survive and grow. The study adopts a qualitative approach using a case study method on selected culinary MSMEs chosen purposively. Data were collected through in-depth interviews, field observations, and documentation, and subsequently analyzed using data reduction, data display, and conclusion drawing techniques. The findings reveal that the innovation capability of culinary MSMEs is reflected in three main dimensions: product innovation, process innovation, and digital marketing innovation. Product innovation is manifested through menu diversification and taste adjustments tailored to local market preferences. Process innovation is reflected in the efficiency of production management and the adoption of technology-based services. Meanwhile, digital marketing innovation is evident in the utilization of social media and e-commerce platforms to expand market reach. These findings indicate that enhancing innovation capability not only improves competitiveness but also strengthens the sustainability of culinary MSMEs amid dynamic market conditions. The implications of this study highlight the importance of training support, access to technology, and collaboration among MSME actors and local government in strengthening innovation capabilities.